Pengaruh Bimbingan Kelompok dengan Teknik Self Management terhadap Disiplin Belajar - Elphisman Zendrato; Justin Foera-era Lase; Hosianna Rodearni Damanik; Famahato Lase (Counseling Milenial (CM), 2025)
Group guidance is an activity carried out by a group of individuals utilizing group dynamics, namely interactions in the form of sharing opinions, responses, suggestions, and so forth. Learning discipline is not only obedience to rules but also the realization of individual awareness to take responsibility for their own learning process. This study aims to determine the significant influence of group guidance using self-management techniques on students’ learning discipline at SMK Negeri 1 Gunungsitoli Alo’oa. This research is a quantitative study. Quantitative research involves the collection and analysis of numerical data with controlled variables, which allows researchers to investigate phenomena and relationships between variables in a structured manner. The results of the hypothesis test using the paired sample t-test with a significance value (Sig. 2-tailed) of 0.001 < 0.05 indicate that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, thus it can be concluded that group guidance using self-management techniques has a significant influence on learning discipline.